(untitled) - Dalal, Priti (London, 2004)
This book is an essential guide to airway management for trainee anaesthetists and intensivists, operating department practitioners and anaesthetic/theatre nurses. Emphasis is given to the basics of airway assessment, how to handle vital emergency procedures and the difficult airway--all situations which will be familiar in any hospital.
Keywords: Trachea,Khí quản,Airway (Medicine),Khí đạo (Y học); Intubation,Đặt ống